Risk factors and complications of manual placental removal after vaginal delivery – how common are additional invasive procedures?. (1st February 2019) - Anteby, Matan; Many, Ariel; Ashwal, Eran; Yogev, Yariv; Shinar, Shiri
Abstract: Purpose: The purpose of this study is to assess risk factors and complications of manual placental removal. Materials and methods: An historical prospective study of all parturients undergoing manual placental removal between 2012 and 2014. Parturients were matched by time of delivery with parturients delivering vaginally with spontaneous placental separation. Multiple gestations, preterm deliveries, incomplete placental separation and uterine malformations were excluded. Delivery characteristics and short-term complications were studied. Telephone questionnaires were conducted to assess the likelihood of invasive procedures performed for retained products of conception (RPOC) up to 12 weeks postpartum. Results: Overall 293 (1.5% of all vaginal deliveries) were complicated by manual placental removal. Independent risk factors included advanced maternal age (odds ratio (OR) 1.08, 95% CI 1.03–1.12), previous manual removal (OR 9.27, 95% CI 3.15–27.31), regional anesthesia (OR 3.49, 95% CI 2.14–5.70), and labor induction (OR 1.80, 95% CI 1.12–2.88). Short-term complications included blood product transfusions (OR 18.26 95% CI 5.37–62.13) and prolonged hospitalization (OR 1.51 95% CI 1.06–2.16). Invasive procedures for removal of RPOC occurred in 12.2% of women in the study groups and in none of the women in the control group ( p  < .001). Conclusions: Manual placental removal harbors short- and long-term complications, including a high likelihood of RPOC necessitating further invasive procedures.